জীবন স্মৃতি - খান, মোবারক হোসেন, ১৯৩৮- (ঢাকা : আগামী প্রকাশনী, 1998)
Autobiography of a Bangladeshi musician, Khāna Mobāraka Hosena, b. 1938.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Khāna, Mobāraka Hosena, -- 1938-; Musicians -- Biography; Musicians -- Bangladesh -- Biography; Bangladesh -- Biography